Exploration of The Social Context of The Pandemic in The Andromeda Strain by Michael Crichton: A Recent Review - Ali, Muhammad Ilham (Fakultas Ilmu Budaya, Universitas Mulawarman, 2024)
This study looks at how this novel depicts a society that is both fascinated by science and terrified. This study in the book